Music Creation Garbebu | Tabuh Kreasi Garbebu - I Made Gede Adi Praginatha Purnama; I Nyoman Kariasa (GHURNITA: Jurnal Seni Karawitan, 2024)
Garbebu's work is a work of musical art that was inspired when the creator saw directly the life events that occurred, namely the incident when a woman was married and carrying a baby in her stomach and seeing how a mother feels and waits to be able to experience pregnancy and have a baby. In other words, this work is inspired by the human life cycle. The human life cycle occurs by combining spermatozoid cells (Kama Petak) with ovarian cells (Kama Bang), which appear in the mother's womb. The process of unification or initial formation until the birth of a baby in a mother's womb is called Garbebu. The expression media used by the creator in expressing the idea of the work is the barungan gamelan Gong Kebyar, including Terompong, kendang cedugan, bebende, and kempli, which are the determining waits in pegongan (lelambatan) works which are still related to tabuh kreasi pepanggulan. This idea is expressed in an intertwining of tones in a musical work by processing musical elements, namely melody, rhythm, tempo, and dynamics, to create a harmonious order. Tabuh kreasi pepanggulan Garbebu uses the Tri Angga structure, which consists of Pengawit, Pengawak/pengadeng, and Pengecet, and the composition of the work is innovated with several parts that remain based on traditional standards. In realizing this Garbebu work, the creator used a creation method that refers to the book Panca Shtiti Ngawi Sani, written by Mr. I Wayan Dibia in 2020, which consists of the Inspiration Stage (Ngawirasa), Exploration Stage (Ngewacak), Conception Stage (Ngarencana), Stage Execution (Ngewangun), and Ngebah/maedeng Stage.